Iodine deficiency among goiter patients in rural South Sudan - Chuot, Chep C.; Galukande, Moses; Ibingira, Charles; Kisa, Nicholas; Fualal, Jane O. (BMC research notes, 2014)
It is estimated that 2.2 billion or approximately 30% of the world’s population live in iodine-deficient areas. In a 2005 study households consuming iodized salt in South Sudan increased from 40% to 73%. Despite this achievement, there are still many goiter cases in rural South Sudan and iodine deficiency remains as a major public health problem in this part of sub Saharan Africa. The purpose of this study therefore was to determine the prevalence of iodine deficiency among rural Southern Sudan goiter patients. Methods: A cross-sectional study was carried out in three South Sudan counties, adults with goiter were from three centers following a mobilization campaign that lasted 4 weeks for free medical care. They were clinically evaluated and completed interviewer administered questionnaires to determine their age, gender, diet, family history, drug history, and medical history. Urine samples were then taken for urinary iodine levels. The outcome was iodine deficiency measured as urinary iodine less than 100 μg per/ L. Multiple logistic regression was used to establish the factors associated with iodine deficiency in South Sudan. Ethical approval was obtained. Results: A total of 286 goitre patients were recruited. The mean age was 38 years (SD 9), 262(92%) were females (F: M ratio 11:1), and 257(90%) were rural- peasants, 25% (20/286) had moderate to severe iodine deficiency. 174 (62%) consumed non-iodized salts.
Keywords: Goiter; Iodine; Deficiency; Rural south Sudan